Checking Blood Sugar Levels at Once, Total Cholesterol and Uric Acid in Health Cadres of Mojowuku Village, Kedamean District - Ahmad, Yuliasmi; Diva, Azhalia; Ningtyas, Risma (UNUSA Press, 2024)
Currently, Indonesia is struggling with the double burden of infectious diseases and non-communicable diseases. One way to control non-communicable diseases is to reduce and control risk factors through early detection (screening). This study aims to determine the picture of the levels of temporary blood sugar, total cholesterol, and uric acid in the Mojowuku Village community. The type of research used was a survey with a Cross Sectional design conducted in Kedamean District, Gresik Regency, East Java Province in July 2023. The sample of this study were 27 respondents with details of the time of checking blood sugar levels, 21 respondents checked total cholesterol levels, 22 respondents and checking uric acid levels, 24 respondents. Sampling using accidental sampling technique with instruments such as lancet pen, alcohol swabs, GCU meter branded Easy Touch, and glucose, cholesterol, and uric acid strips. This study uses Univariate Analysis with Descriptive test and Compare Means One Sample T Test. Based on the results of the study, the average blood sugar level in the Mojowuku Village community was in the normal category at 119.5 mg/dL, the total cholesterol level was 157.6 mg/dL and the uric acid level in the normal category reached 6.0 mg/dL. Local health centers can activate Posbindu cadres and conduct early detection so that risk factors for non-communicable diseases can be controlled.